Primum non nocere; It’s time to consider altitude training as the medical intervention it actually is! - Van Cutsem, Jeroen; Pattyn, Nathalie (Frontiers in Psychology, 2022)
Sleep is one of the most important aspects of recovery, and is known to be severely affected by hypoxia. The present position paper focuses on sleep as a strong moderator of the altitude training-response. Indeed, the response to altitude training is highly variable, it is not a fixed and classifiable trait, rather it is a state that is determined by multiple factors (e.g., iron status, altitude dose, pre-intervention hemoglobin mass, training load and recovery). We present an overview of evidence showing that sleep, and more specifically the prolonged negative impact of altitude on the nocturnal breathing pattern, affecting mainly deep sleep and thus the core of physiological recovery during sleep, could play an important role in intra- and interindividual variability in the altitude training-associated responses in professional and recreational athletes. We conclude our paper with a set of suggested recommendations to customize the application of altitude training to the specific needs and vulnerabilities of each athlete (i.e., primum non nocere). Several factors have been identified (e.g., sex, polymorphisms in the TASK2/KCNK5, NOTCH4 and CAT genes and pre-term birth) to predict individual vulnerabilities to hypoxia-related sleep-disordered breathing. Currently, polysomnography should be the first choice to evaluate an individual’s predisposition to a decrease in deep sleep related to hypoxia. Further interventions, both pharmacological and non-pharmacological, might alleviate the effects of nocturnal hypoxia in those athletes that show most vulnerable.